Proof that in an efficient market, event studies can provide no systematic guidance for revision of accounting standards and disclosure policy for the purpose of maximizing shareholder wealth* - SUNDER, SHYAM (Contemporary Accounting Research, 1989)
Abstract. A systematic revision of accounting standards and disclosure policy on the basis of evidence obtained from event studies conducted in an efficient stock market is shown to be an ineffective means of maximizing shareholder wealth. Résumé. Une réision systématique des normes de comptabilité et des conventions relatives à la présentation de l'information à partir de l'information recueillie à la suite d'études d'événements menées dans un marché boursier efficient se révèle inefficace lorsqu'il s'agit de maximiser la richesse des actionnaires.